Mixed Mycobacterium avium subspecies avium and M avium subspecies paratuberculosis infection in a wild red deer (Cervus elaphus) in Belgium. Issue 2 (24th June 2020) - Volpe, Rosario; Fett, Thomas; Cassart, Dominique; Godfroid, Jacques; Linden, Annick
Abstract : This report describes a mixed Mycobacterium avium subspecies avium and M avium subspecies paratuberculosis infection in a free‐ranging red deer ( Cervus elaphus ). The gross presentation was consistent with clinical paratuberculosis as previously reported in red deer and for other ruminants, with poor body condition, diarrhoea and mesenteric lymphadenitis. However, this animal presented unusual lung lesions, with necrosis and calcification similar to those reported for Mycobacterium bovis infection in wild and domestic ruminants. A mixed M avium subspecies avium and M avium subspecies paratuberculosis was shown by quantitative PCR (qPCR) performed on digestive tract samples. In addition, M avium subspecies avium was also detected in the respiratory tract (lungs and bronchial lymph nodes) by qPCR. These results were confirmed by classical bacteriology. Lesions induced by those mycobacteria cannot be differentiated from M bovis lesions. This point is particularly important with regards to increasing interactions between livestock and wild animals.